Albizia hasslerii (Chodat) Burkart: maturação e fisiologia de sementes e produção de mudas - Ristau, Ana Carolina Pinguelli (2019)
Knowing the harvest season of native forest species is fundamental, due to the possibility of planning this operation and later handling and use, besides the practice of associating maturity with the color of the fruit. In addition, the seeds may alter the performance of the physiological potential, according to the phytogeographic distribution of the matrices, which showed adaptation to the local edaphoclimatic conditions, which makes it necessary to study at different harvesting sites. The present work had as objective to determine the time when the seeds of Albizia hasslerii (Chodat) Burkart reach high physiological potential and additionally verify the quality of seeds of different origins on the quality of seedlings produced. To determine the time of seed harvest, fruits were harvested in Marechal Cândido Rondon and visually classified in four maturation stages by fruit color. The variables analyzed in the seeds included morphological characteristics, germination and vigor. In the studies of physiological potential and seedling quality among the provenances, the fruits were collected in Diamante D'Oeste, Santa Helena, Marechal Cândido Rondon and Sarandi. Afterwards, the mass of one thousand seeds, germination test, vigor (germination speed index and respiration rate, emergence rate, emergency speed index), as well as seedling production (conducted with irrigation and without irrigation), where height, collection diameter, root electrolyte loss, total dry matter mass and Dickson quality index were evaluated. In addition to root regeneration potential, in seedlings produced in parallel, under irrigation. The fruits of stages 3 and 4 showed higher germination (69% and 78%) and emergence (38% and 36%), lower water content (59.2% and 15.5%) and higher mass content of dry matter (0.48 g and 0.51 g), since these are indicators of the best fruit picking time considering orthodox seeds. Seeds obtained from green fruits presented low germination (11%) and vigor, high water content (64.27%) and low dry matter content (0.43 g). Regarding the seeds harvested from different sources, it was possible to verify that the municipality of Santa Helena presented seeds with high physiological potential. These seeds had the highest percentage of total germination (100%) and germinated faster (mean time of 9.6 days and germination rate index of 3.29), in addition to having a higher respiration rate (5.35 μmmol CO2 g-1). The seeds harvested in the other municipalities presented low physiological potential. Regarding the seedlings, of all parameters, only the root regeneration potential was significant, where seedlings from Santa Helena seeds had a higher average (89.4 mg/seedling). Seeds of A. hasslerii present high physiological potential, when the fruits are 100% brown (stage 4) and when the fruits are> 50% <100% brown (stage 3) can also be harvested. Therefore the color of the fruits is a good indicator of physiological maturity for this species. The seeds of A. hasslerii were influenced by the place of harvest of the seeds. As well as, the physiological potential of the seeds of all origins influenced the potential of root regeneration.